Medieval Rus' and early modern Russia : texts and contexts, essays in honour of Simon C. Franklin - Franklin, Simon; Torres Prieto, Susana; Franklin, Andrei (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Research on the East Slavs in the medieval period has considerably changed since the collapse of the Soviet Union. The emergence of new states forced a rethinking of many aspects of the history and culture of the early East Slavs as the subject became increasingly disentangled from the umbrella of Byzantine studies and fruitful collaboration was fostered between scholars worldwide. This book, which brings together scholars from Russia, Ukraine, western Europe and North America, of several generations, presents a broad overview of the main results of the last three decades of research and mutual collaboration. This is important work, providing a much-needed counterbalance to studies of western Europe in the period, which has been the main focus of study, with the lands of the East Slavs relatively neglected"--
List of figures -- List of contributors -- Foreword / by Andrei Franklin and Susana Torres Prieto -- List of abbreviations -- List of libraries and archives -- Leo VI and the transformation of Byzantine strategic thinking about the Rus' / Monica White -- Who was 'Theodore the Rhos from a family of emperors', the owner of the stone from the Holy Sepulchre? / Oleksiy Tolochko -- Cosmos, calendars and medical advice in the miscellanies of the Trinity Lavra of St. Sergius and their late Byzantine counterparts (14th-early 16th centuries) / Ann-Laurance Caudano -- Holy foolishness and gender transgression in Russian hagiography from the Middle Ages to modernity / Nick Mayhew -- Some unnoticed Greek quotes in old Russian Chronicles / Sergey A. Ivanov -- Retranslating the Rus' Primary Chronicle: perspectives on Horace Lunt's new rendering / Michael S. Flier -- Two emperors of the princess Olga's visit to Constantinople: Constantine VII Porphyrogenitos versus John Tzimiskes in the copies of the Rus' Primary Chronicle / Tatiana Vilkul -- Patriarch Germanus II of Constantinople and the Slavic world / Maria V. Korogodina -- Thoughtful agglomeration: late Byzantine sources for Muscovite ceremonial / Alexandra Vukovich -- Boris Godunov and his family in the mirror of medieval Russian polyonymy / Anna Litvina and Fjodor B. Uspenskij -- "I must be cruel only to be kind": towards a literary history of Kyiv graffito No. 108 / Aleksey A. Gippius -- Muscovite acquisition of books from Poland in the late 1640s-Early 1650s / Daniel C. Waugh and Olena Janssen -- The Codex in early Rus' between the 11th-15th centuries: variations of form and variations of function / Dmitrii Bulanin -- Sofiia Vitovtovna's dance: the wedding of Vasilii II in Russian cultural memory / Sergei Bogatyrev -- Revolution in the pictosphere: the Ukrainian Baroque and Muscovite reception / Valerie Kivelson -- Index.
Keywords: Slavs, Eastern -- History; Slavs, Eastern -- Historiography; Russia -- History -- To 1533 -- Sources; Russia -- History -- To 1533 -- Historiography; Kievan Rus -- History -- Sources; Kievan Rus -- Historiography; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research